Small molecule inhibitors in the treatment of cerebral ischemia. (April 2014) - Flores, Jerry J; Zhang, Yang; Klebe, Damon W; Lekic, Tim; Fu, Weiling; Zhang, John H
<x xml:space="preserve">Abstract</x> Introduction: Stroke is the world's second leading cause of death. Although recombinant tissue plasminogen activator is an effective treatment for cerebral ischemia, its limitations and ischemic stroke's complex pathophysiology dictate an increased need for the development of new therapeutic interventions. Small molecule inhibitors (SMIs) have the potential to be used as novel therapeutic modalities for stroke, since many preclinical and clinical trials have established their neuroprotective capabilities. Areas covered: This paper provides a summary of the pathophysiology of stroke as well as clinical and preclinical evaluations of SMIs as therapeutic interventions for cerebral ischemia. Cerebral ischemia is broken down into four mechanisms in this article: thrombosis, ischemic insult, mitochondrial injury and immune response. Insight is provided into preclinical and current clinical assessments of SMIs targeting each mechanism as well as a summary of reported results. Expert opinion: Many studies demonstrated that pre- or post-treatment with certain SMIs significantly ameliorated adverse effects from stroke. Although some of these promising SMIs moved on to clinical trials, they generally failed, possibly due to the poor translation of preclinical to clinical experiments. Yet, there are many steps being taken to improve the quality of experimental research and translation to clinical trials.